A comparative study of numerical modelling techniques for the fracture of brittle materials with specific reference to glass. (1st December 2017) - Wang, Xing-er; Yang, Jian; Liu, Qing-feng; Zhang, Yang-mei; Zhao, Chenjun
Highlights: Four different numerical approaches for modelling the fracturing of brittle materials were compared for efficiency and applicability. The dynamic fracture response of a monolithic glass beam subjected to the hard body impact was numerical modelled. The discontinuum based numerical approaches are more favourable than the continuum based ones in analysing the cracking patterns of glass subject impact. FEM/DEM has high potential for modelling the dynamic damage/failure of brittle materials. Abstract: This paper presents a comparative study on the available numerical approaches for modelling the fracturing of brittle materials. These modelling techniques encompass the finite element method (FEM), extended finite element method (XFEM), discrete element method (DEM) and combined finite-discrete element method (FEM/DEM). This study investigates their inherent weaknesses and strengths for modelling the fracture and fragmentation process. A comparative review is first carried out to illustrate their fundamental principles as well as the advantages for the modelling of cracks, followed by the state-of-the-art trial application in the example cases. An example of a glass beam subjected to low velocity hard body impact is examined as a plane stress problem. By evaluating the applicability of different models, the most desirable model for the entire dynamic fracture response is identified, and this is found to be the FEM/DEM. The FEM/DEM model is further examined by comparing results with the experimental data from high velocity and oblique impact tests. The study reveals that the FEM/DEM yields the most satisfactory results when modelling the dynamic fracture process of brittle materials such as glass.